Pelatihan Komunikasi Persuasif Guna Meningkatkan Kompetensi Komunikasi Pengurus Lembaga Swadaya Masyarakat “Kakak Asuh” - Mauly Arzak Julika; Dwi Ulina Sari; Mahisa Dwi Prastowo (Inovasi Sosial : Jurnal Pengabdian Masyarakat, 2025)
In addition to improving interpersonal communication skills, this training also emphasized the importance of strategic communication in the context of advocacy and social mobilization. NGO administrators were trained to design campaign messages tailored to audience segments, including potential donors, corporate partners, and government stakeholders. An understanding of the importance of framing and emotional appeal was also emphasized, so that the messages delivered were not only informative but also able to inspire empathy and concrete action from the audience. During the training process, participants were also equipped with a basic understanding of digital communication, particularly in utilizing social media platforms as a tool to expand the reach of messages. Creative content strategies, effective posting scheduling, and the use of visual storytelling were introduced so that NGO administrators could build a positive image of their institutions in the digital space. These skills are crucial considering that the dynamics of public communication today are influenced by the speed and reach of social media.The positive impact of this activity was felt not only individually, but also institutionally.The NGO "Kakak Asuh" began to show an increase in public engagement through social media, an increase in the number of new volunteers, and the opening of opportunities for partnerships with external parties. This demonstrates that persuasive communication is not merely a means of conveying a message, but also a strategy for building strong, credible, and sustainable relationships with the wider community. Going forward, the sustainability of this training program is designed through a system of ongoing mentoring and support. This approach is expected to strengthen the implementation of the communication strategies learned and enable a comprehensive transformation of organizational communication. Thus, this PKM activity will not only have a short-term impact but also build a solid communication foundation to support the NGO's social mission in the future.